Bilayer Thin Films That Combine Luminescent and Spin Crossover Properties for an Efficient and Reversible Fluorescence Switching [Articol] - Palamarciuc, Oleg; Bas, Alin-Caprian (MDPI, 2019)
We report on the vacuum thermal deposition of bilayer thin films of the luminescent complex Ir(ppy)3, tris[2-phenylpyridinato-C2,N]iridium(III), and the spin crossover complex [Fe(HB(tz)3)2], bis[hydrotris(1,2,4-triazol-1-yl)borate]iron(II). Switching the spin state of iron ions from the low spin to the high spin state around 337 K leads to a reversible jump of the luminescence intensity, while the spectrum shape and the luminescence lifetime remain unchanged. The luminescence modulation occurs due to the di erent UV light absorption properties of the iron complex in the two spin states and its magnitude can therefore be precisely adjusted by varying the film thickness. These multilayer luminescence switches hold potential for micro- and nanoscale thermal sensing and imaging applications.
Keywords: spin crossover; luminescence; thin films